A Probabilistic Model for the Flexural Capacity of Reinforced Concrete Structures Strengthened with Prestressed CFRP Plates. Issue 5 (May 2015) - Liu, Yang; Peng, Hui; Cai, C.S.
Strengthening concrete structures with prestressed carbon fiber reinforced polymer (CFRP) materials has gained popularity in recent years due to its ability to efficiently utilize the material's strength. However, the reliability of structures strengthened with prestressed CFRP laminates is a key issue. In this paper the statistical characteristics of design variables of reinforced concrete beams strengthened with prestressed CFRP plates are assessed. Accounting for the gradient effects, the Weibull distribution is used to describe the probability distribution function of the size and stress. The loss of prestressing force is analyzed considering the prestressing method. The probabilistic models of the flexural capacity are established for the three failure models, and the influence of variables on the flexural capacity is also studied. The probabilistic model derived in this paper can be used as the theoretical basis of reliability analysis and safety assessment of structures strengthened with CFRP materials.